2021
DOI: 10.1088/1361-665x/ac26e6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of proposed integrated control strategies based on performance and positioning of MR dampers on shaking table

Abstract: Most of the studies in the field of structural control are focused on maximizing the performance of control devices without taking into consideration the complex dynamic response of the structure, computational efficiency, performance flexibility, and feedback reliability. Also, the location algorithm of energy dissipation should be concatenated with the control strategy, for effective structural control of multi-story structures. Moreover, in recent years, non-contact measurements using digital image correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Wani et al [16] suggested two response-basedadaptive control techniques for reducing inter-story drift and acceleration response. Control techniques are combined with the device location algorithm to determine the optimal magnetorheological damper configuration and controls system design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Wani et al [16] suggested two response-basedadaptive control techniques for reducing inter-story drift and acceleration response. Control techniques are combined with the device location algorithm to determine the optimal magnetorheological damper configuration and controls system design parameters.…”
Section: Introductionmentioning
confidence: 99%